Therapy of Ulcerated Hemangiomas. Issue 4 (July 2013) - McCuaig, Catherine C.; Cohen, Lynn; Powell, Julie; Hatami, Afshin; Marcoux, Danielle; Maari, Catherine; Caouette-Laberge, Louise; Bortoluzzi, Patricia; Ondrejchak, Sandra; Dubois, Josée
Background: Cutaneous ulceration is the most common complication of infantile hemangiomas (IHs) seen in a pediatric dermatology practice. Objective: The most effective treatments in our experience are compared to those in the current literature. Methods: The study was a retrospective chart review of therapy of 169 ulcerated IHs at a tertiary care pediatric hospital and a literature review. Results: Combination therapy was the rule. Local wound care was required in all, pain management in 72%, pulsed dye laser in 42%, infection control in 38%, diminution of the hemangioma through systemic therapy in 36%, and suppression of bleeding in 2%. Limitations: A retrospective review compared to a case-control study has inherent bias. In addition, our cases were all at a tertiary referral center. Conclusion: All ulcerated IHs benefit from local barrier creams or dressings. Pulsed dye laser, antibiotics, topical morphine 0.1% in hydrogel, topical becaplermin, and, most importantly, systemic therapy (especially propranolol) to reduce the hemangioma may be useful.